Challenges of Using Drones in Marketing for Cultural Tourism in Syria ( Survey Study at the Directorate of Tourism and the Directorate of Culture in Lattakia Governorate( - سعيد , بلسم; فــــداء الشّــــــيخ حســـن ,; نجوى عيسى محمود, (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aimed to identify the most important obstacles to the use of Drones in the marketing of cultural tourism, whether they are financial, legal, technical or human obstacles. The deductive approach was relied on as a general method of thinking, and on the descriptive-analytical approach to describe the concepts of research and analysis of the data collected by means of a questionnaire distributed to workers in the field of marketing in the directorates of tourism and culture in Lattakia governorate, who numbered 51 individuals, The SPSS 20 statistical program was relied on as a tool for data analysis and testing research hypotheses using arithmetic averages and the One-Sample Test. The study reached many results, the most important of which was the weak marketing activity of cultural tourism in the districts under study due to the failure of the senior management to adopt modern strategies and methods of marketing and the lack of training and qualification of human cadres to follow up on marketing developments, in addition to the lack of encouragement of management to adopt and present attractive marketing programs for cultural tourism. As well as the existence of multiple financing obstacles that negatively affect the possibility of adopting the use of drones as a modern and sophisticated means of marketing for cultural tourism, due to the lack of financial capabilities necessary to secure equipment and supplies from drones, lighting devices, cameras, computers and software necessary for its work.